Testicular tissue cryopreservation for fertility preservation in prepubertal and adolescent boys: A 6 year experience from a Swiss multi-center network - Moussaoui, Dehlia; Surbone, Anna; Adam, Cécile; Diesch-Furlanetto, Tamara; Girardin, Céline; Bénard, Julie; Vidal, Isabelle; Bernard, Fanette; Busiah, Kanete; Bouthors, Thérèse; Primi, Marie-Pierre; Ansari, Marc; et al. (Frontiers in Pediatrics, 2022)
Testicular tissue cryopreservation is the only option of fertility preservation in prepubertal boys. While it is considered experimental, since procedures to obtain mature sperm from prepubertal testicular tissue are still under development, testicular tissue cryopreservation programs have emerged worldwide. Our aim was to study the feasibility and safety of a program of testicular tissue cryopreservation in prepubertal and adolescent boys facing gonadotoxic treatment in three University hospitals in Switzerland. Testicular tissue cryopreservation was accepted by 90% of families, with a total of 35 patients included. The average patient age was 8.5 years (range 7 months to 18.5 years). Malignancies were the most common diagnosis (31 patients, 88.6%) with 16 (45.7%) solid tumors and 15 (42.9%) hematological malignancies. Four (11.4%) patients had a benign condition. The main indication for testicular tissue cryopreservation was conditioning for hematologic stem cell transplantation (25 patients, 71.4%). There were two minor adverse events and none of them required medical treatment or surgical revision. Tumoral cells were found in one testicular biopsy of a leukemic patient. Five patients died during follow-up. Our data demonstrate the feasibility and safety of a program of testicular tissue cryopreservation coordinated by a multidisciplinary team of fertility preservation. Despite the experimental aspect of the procedure, the acceptation rate was high, which highlights the willingness of families and patients to participate in testicular tissue cryopreservation.